Nailfold Capillaroscopy: A Non-invasive Tool for Early Detection of Microvascular Alterations in Children with Type 1 Diabetes Mellitus - Akın Kağızmanlı, Gözde; Aydın, Tuncay; Yüksek Acinikli, Kübra; İşgüder, Rana; Kızıldağ Karabacak, Zehra; Demir, Korcan; Böber, Ece; Ünsal, Şevket Erbil; Abacı, Ayhan (Journal of clinical research in pediatric endocrinology, 2025)
Nailfold capillaroscopy (NC) is a non-invasive tool that can detect microvascular changes in the early stages of vascular disease. We aimed to assess capillary microarchitecture in children with type 1 diabetes mellitus (T1DM) and its relationship with clinical characteristics, laboratory findings, and glycemic control. We included 55 children with T1DM (aged 6-18 years, diagnosed for at least one year) and 55 age- and sex-matched healthy controls. For all patients with T1DM, data on diabetes duration were collected, and the average HbA1c values were calculated by taking the mean of the HbA1c levels measured at three-month intervals during routine clinical assessments over the past year. In patients using 24-hour continuous glucose monitoring (CGM) devices, glycemic data from the previous 3 months were analyzed. The capillaroscopic findings were evaluated by two different researchers with experience in the field of pediatric rheumatology. Capillaroscopic parameters were compared based on glycemic control (HbA1c ≥7.5% vs. <7.5%), disease duration (<5 vs. ≥5 years), time in range (TIR ≥70% vs. <70%), and glucose variability (CV ≤36% vs. >36%). The median age of patients with T1DM was 14.5 (11.3-17.2) years, with a median disease duration of 3.8 (2.3-6.7) years. Compared to controls, patients with T1DM had significantly lower capillary density and more frequent dilated, tortuous, cross-linked, and abnormal capillaries (p<0.001, p<0.001, p<0.001, p=0.01, and p=0.03, respectively). Capillary density was significantly lower in patients with poor glycemic control (p<0.001) and those with longer disease duration (p=0.02). A negative correlation was observed between capillary density and disease duration (r=-0.3, p=0.02). After adjusting for age, gender, BMI, and diabetes duration, capillary density remained negatively correlated with average HbA1c (r= -0.4, p=0.004). Among CGM users (n=22), capillary density showed a positive correlation with TIR (r=0.5, p=0.04), even after adjustment for confounders. Children with T1DM exhibited significantly higher microvascular changes, mostly associated with poor glycemic control, compared to healthy controls. NC can be a useful technique for detecting early alterations in the capillary structures of children with T1DM, even in the absence of microvascular complications.